Implementasi Program Kampung Keluarga Berkualitas di Kelurahan Meranti Pandak Kota Pekanbaru - Alex Sihol Batubara; Ali Yusri; Abdul Sadad (Universitas Warmadewa, 2024)
Quality Family Village (Kampung KB) is a rebranding of the Family Planning program. This occurred because based on the results of the 2018 evaluation, the function of the Family Planning Village had not run optimally as expected. The selection of Meranti Pandak Village as one of the Quality Family Villages (Kampung KB) in Pekanbaru City was based on 3 (three) criteria, the main one being the achievement of low family planning and Pre-Prosperous Families, from the regional criteria namely poor, remote, slum and border, and from the criteria across sectors, namely low education and inadequate infrastructure. This research aims to determine the implementation of the Quality Family Village Program in Meranti Pandak Village, Pekanbaru City. The theory used is program implementation, according to Charles O Jones in (Piay et al., 2023) which is divided into three indicators, namely organization, interpretation and application. This type of research is qualitative with a descriptive approach. The data collection techniques include observation, interviews and documentation. The data analysis used is data collection, data reduction, and drawing conclusions. The results obtained in the research explain that the implementation of the Quality Family Village Program in Meranti Pandak Village has not gone well.